2020
DOI: 10.1002/jlb.5mr0120-377r
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the connection between eosinophils and obesity

Abstract: Obesity affects more than 650 million adults worldwide and is a major risk factor for a variety of serious comorbidities. The prevalence of obesity has tripled in the past forty years and continues to rise. Eosinophils have recently been implicated in providing a protective role against obesity. Decreasing eosinophils exacerbates weight gain and contributes to glucose intolerance in high fat diet‐induced obese animals, while increasing eosinophils prevents high‐fat diet‐induced adipose tissue and body weight g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…It has also been suggested that eosinophils may mediate glucose homeostasis and energy expenditure. However, the role of eosinophils in obesity is a matter of debate with studies showing conflicting findings, some suggesting that they protect from obesity while others suggest the opposite [113].…”
Section: Innate and Adaptive Immune Systemsmentioning
confidence: 99%
“…It has also been suggested that eosinophils may mediate glucose homeostasis and energy expenditure. However, the role of eosinophils in obesity is a matter of debate with studies showing conflicting findings, some suggesting that they protect from obesity while others suggest the opposite [113].…”
Section: Innate and Adaptive Immune Systemsmentioning
confidence: 99%
“…It is also worth mentioning that leptin promotes while adiponectin attenuates eotaxin-induced human eosinophil adhesion and chemotaxis (55, 218,219). Nevertheless, enhancing AT eosinophil abundance is debated since several studies demonstrated no beneficial or even negative outcomes of this approach (220). Required for the production of ROS LPS-treated mouse bone marrow-derived neutrophils treated with Antimycin A or myxothiazol (190) Required for migration Polg CRISPR/Cas9-mediated neutrophil-specific knockout in Zebra fish (191) Pentose phosphate pathway ⇑ Required for NETosis Amyloid fibril-and phorbol myristate acetate-stimulated human neutrophils (192) Required for ROS generation and NETosis G6PD-deficient patients G6PD-deficient mice (193,194) TCA cycle ⇑ Required for chemotaxis Isocitrate dehydrogenase 1 mutant mice (195) Required for differentiation Mouse Atg5-deficient neutrophils and an in vitro model of differentiating neutrophils (196) Lipogenesis ⇑ Required for differentiation Atg7-deficient neutrophil precursors (197) Required for neutrophil maintanence FASlox/lox-Rosa26-CreER mice (198) Glutamine metabolism It was suggested that circulating eosinophils display a greater metabolic flexibility in comparison to neutrophils (200,201).…”
Section: Eosinophilsmentioning
confidence: 99%
“…It has been shown that, no matter the metabolic state displayed by the adipose micro-environment, both the homeostatic functions of eosinophils and the general mechanisms regulating eosinophil presence within adipose tissue are alike; including the mediation by a common tripod of type 2 innate lymphoid cells (ILC2s), IL-5, and eotaxin (4,5). However, the multiplicity of adipose micro-environmental factors potentially capable of establishing adipose eosinophilia and/or properly activate eosinophil functions is far more abundant and obviously not restricted to these three key players, and as shown here, may involve leptin as an additional molecular modulator.…”
Section: Discussionmentioning
confidence: 99%
“…It seems definitive that eosinophilia is a hallmark of lean adipose niches and that eosinophils counteract the obesity related chronic inflammation ( 18 , 48 ). This knowledge is derived from a large body of data using C57BL/6 mouse experimental models of obesity which established the reduction of homeostatic eosinophils in adipose tissue undergoing metabolic syndrome ( 4 , 5 ). Nevertheless, Lee et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation